Extended Hildebrand solubility approach applied to some structurally related sulfonamides in ethanol + water mixtures - Daniel R. Delgado; María Á. Peña; Fleming Martínez (Revista Colombiana de Química, 2016)
Extended Hildebrand Solubility Approach (EHSA) was applied to evaluate the solubility of sulfadiazine, sulfamerazine, and sulfamethazine in some ethanol + water mixtures at 298.15 K. Reported experimental equilibrium solubilities and some fusion properties of these drugs were used for the calculations. In particular, a good predictive character of EHSA (with mean deviations lower than 3.0%) has been found by using regular polynomials in order four correlating the interaction parameter W with the Hildebrand solubility parameter of solvent mixtures without drug. However, the predictive character of EHSA was the same as that obtained by direct correlation of drug solubilities with the same descriptor of polarity of the cosolvent mixtures.